Mechanisms of productive folding and endoplasmic reticulum-associated degradation of glycoproteins and non-glycoproteins - Ninagawa, Satoshi; George, Ginto; Mori, Kazutoshi (Biochimica et biophysica acta. General subjects, 2021)
The quality of proteins destined for the secretory pathway is ensured by two distinct mechanisms in the endoplasmic reticulum (ER): productive folding of newly synthesized proteins, which is assisted by ER-localized molecular chaperones and in most cases also by disulfide bond formation and transfer of an oligosaccharide unit; and ER-associated degradation (ERAD), in which proteins unfolded or misfolded in the ER are recognized and processed for delivery to the ER membrane complex, retrotranslocated through the complex with simultaneous ubiquitination, extracted by AAA-ATPase to the cytosol, and finally degraded by the proteasome. We describe the mechanisms of productive folding and ERAD, with particular attention to glycoproteins versus non-glycoproteins, and to yeast versus mammalian systems. Molecular mechanisms of the productive folding of glycoproteins and non-glycoproteins mediated by molecular chaperones and protein disulfide isomerases are well conserved from yeast to mammals. Additionally, mammals have gained an oligosaccharide structure-dependent folding cycle for glycoproteins. The molecular mechanisms of ERAD are also well conserved from yeast to mammals, but redundant expression of yeast orthologues in mammals has been encountered, particularly for components involved in recognition and processing of glycoproteins and components of the ER membrane complex involved in retrotranslocation and simultaneous ubiquitination of glycoproteins and non-glycoproteins. This may reflect an evolutionary consequence of increasing quantity or quality needs toward mammals. The introduction of innovative genome editing technology into analysis of the mechanisms of mammalian ERAD, as exemplified here, will provide new insights into the pathogenesis of various diseases. •Quality control of proteins is essential for life.•The mechanism of folding of proteins in the endoplasmic reticulum (ER) is summarized.•The mechanism of ER-associated degradation of misfolded proteins is then summarized.•Advances on recognition and processing of misfolded glycoproteins are highlighted.